Pengaruh Model Pembelajaran Kooperatif Tipe Make A Terhadap Motivasi dan Hasil Belajar Materi Pertidaksamaan Linear Satu Variabel Kelas VII SMPN 3 Mataram Tahun Ajaran 2023/2024 - Nufus, Hayatul; Baidowi, Baidowi; Humaira Salsabila, Nilza; Hikmah, Nurul (Mandalika Mathematics and Educations Journal, 2024)
The purpose of this study was to determine the effect of the cooperative learning model type make a match on the motivation and learning outcomes of mathematics in class VII students of SMPN 3 Mataram. The research design used is Quasi Experimental Design. The sampling technique used is probability sampling where class VII-1 is the control class and VII-2 is the experimental class. Based on the results of the study, the average score of the mathematics learning motivation of students in the experimental class is 61.3 with a high category, while the control class got an average score of 42.52 with a medium category. The results of the study, the average value of the mathematics learning outcomes of students in the experimental class was 75.27 with a learning completion percentage of 70%. While the control class got an average score of 51.23 with a learning completion percentage of 9.68%. The result of the t-test of 2 independent show that there is an effect of the cooperative learning model type make a match on the motivation and learning outcomes of class VII students of SMPN 3 Mataram.